Responses to chemical cross-talk between the Mycobacterium ulcerans toxin, mycolactone, and Staphylococcus aureus - Laxmi Dhungel (Nature Portfolio, 2021)
Abstract Buruli ulcer is a neglected tropical disease caused by the environmental pathogen, Mycobacterium ulcerans whose major virulence factor is mycolactone, a lipid cytotoxic molecule. Buruli ulcer has high morbidity, particularly in rural West Africa where the disease is endemic. Data have shown that infected lesions of Buruli ulcer patients can be colonized by quorum sensing bacteria such as Staphylococcus aureus, S. epidermidis, and Pseudomonas aeruginosa, but without typical pathology associated with those pathogens’ colonization. M. ulcerans pathogenesis may not only be an individual act but may also be dependent on synergistic or antagonistic mechanisms within a polymicrobial network. Furthermore, co-colonization by these pathogens may promote delayed wound healing, especially after the initiation of antibiotic therapy. Hence, it is important to understand the interaction of M. ulcerans with other bacteria encountered during skin infection. We added mycolactone to S. aureus and incubated for 3, 6 and 24 h. At each timepoint, S. aureus growth and hemolytic activity was measured, and RNA was isolated to measure virulence gene expression through qPCR and RNASeq analyses. Results showed that mycolactone reduced S. aureus hemolytic activity, suppressed hla promoter activity, and attenuated virulence genes, but did not affect S. aureus growth. RNASeq data showed mycolactone greatly impacted S. aureus metabolism. These data are relevant and significant as mycolactone and S. aureus sensing and response at the transcriptional, translational and regulation levels will provide insight into biological mechanisms of interspecific interactions that may play a role in regulation of responses such as effects between M. ulcerans, mycolactone, and S. aureus virulence that will be useful for treatment and prevention.